Theoretical considerations about the body and the phenomenon of pain in Nasio and Le Poulichet: from image to body in negative - Galvão, Laís Augsten [UNESP]; Bocchi, Josiane Cristina [UNESP] (FapUNIFESP (SciELO), 2023)
This article discusses the role of the body and body image in the phenomenon of physical pain from J.-D. Nasio and Sylvie Le Poulichet. It addresses the status of the body through a phenomenon very present in contemporary subjectivities, as the problem of pain, such as the problem of pain. The affect of pain is little studied in psychosomatic schools, as well as in psychoanalysis. Nasio and Le Poulichet present their own perspectives on the process of pain and understanding of the body and image. They incorporated, each one in their own way, the legacies of the Freudian thought, as well as the Lacanian referential. For one of the authors, the body is more connected to the image and the identifications of the self, while for the other, the body is the place of an excess of sexual and narcissistic order.
Consideraciones teóricas sobre el cuerpo y el fenómeno del dolor en Nasio y Le Poulichet: de la imagen al cuerpo en negativo
Considerátions théoretiques sur le corps et le phénomene de la douleur à Nasio et Le poulichet: de l’image au corps en négatif
Keywords: Body; image body; psychoanalysis; psychosomatic